Influence of morning versus midnight initiation of induction of labour in late-term pregnancy on perinatal outcome and time of birth - Danijel Bursać; Katja Vince; Ratko Matijević (Medical Network, 2019)
Objective. The aim of this study was to assess and compare morning vs. midnight initiation of induction of labor (IOL) on time of birth and perinatal outcome. Study Design. A retrospective study performed at University Hospital Merkur, Zagreb, Croatia; in period between 2006 to 2017. The participants were low-risk nulliparous women with gestational age over 41 weeks who had labor induced by a prostaglandin E2 analogue dinoprostone applied intracervically. Two groups were compared; the first one had IOL initiated in the morning and the second one at midnight. Results. A total of 206 pregnant women were included in the study. Women with IOL starting at midnight (n=103) gave birth more often during daytime (7am-6.59pm) compared to women with IOL starting in the morning (n=103) (p<0.01). The midnight group also gave birth more often during regular hospital working hours (7.30am-3.30pm), but this result was not statistically significant (p=0.091). The rate of epidural analgesia was higher among women in the midnight group, while no other differences were observed in predefined perinatal outcome between the two groups. Conclusions. Initiation of IOL at midnight compared to morning results in giving birth more often during daytime. This presents a favourable option for reducing out of hours and night work.